2018
DOI: 10.1007/s00122-018-3125-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimal cross selection for long-term genetic gain in two-part programs with rapid recurrent genomic selection

Abstract: Key message Optimal cross selection increases long-term genetic gain of two-part programs with rapid recurrent genomic selection. It achieves this by optimising efficiency of converting genetic diversity into genetic gain through reducing the loss of genetic diversity and reducing the drop of genomic prediction accuracy with rapid cycling. AbstractThis study evaluates optimal cross selection to balance selection and maintenance of genetic diversity in two-part plant breeding programs with rapid recurrent genom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
123
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(124 citation statements)
references
References 38 publications
1
123
0
Order By: Relevance
“…The results presented here show that incorporating more breeding cohorts in the training set is beneficial in a conventional breeding program with a long generation interval. A recent study by Gorjanc et al (2018) investigates the response in a rapid cycling program which uses genomic selection to quickly identify parents.…”
Section: Discussionmentioning
confidence: 99%
“…The results presented here show that incorporating more breeding cohorts in the training set is beneficial in a conventional breeding program with a long generation interval. A recent study by Gorjanc et al (2018) investigates the response in a rapid cycling program which uses genomic selection to quickly identify parents.…”
Section: Discussionmentioning
confidence: 99%
“…simulation study also suggests that the probability of success in a breeding program could be achieved with fewer crosses more carefully chosen and bigger segregating populations. This topic has recently been discussed by Gorjanc et al [36], when they simulated the results of applying an optimal cross selection scheme to balance selection and maintenance of genetic diversity for breeding programs under a recurrent genomic selection scheme. They showed the benefits of the optimal cross selection, and the positive implications for maintaining genetic diversity and genomic prediction accuracy in the long term.…”
mentioning
confidence: 99%
“…Stochastic simulations are becoming widely used to explore the efficiency of genomic selection in single species breeding only (e.g. Muleta et al 2019;Gorjanc et al 2018;Gaynor et al 2017), but to our knowledge our use of simulations to explore genomic selection's value for intercrop breeding is unique. Through simulations, we have shown that intercrop breeding programs using genomic selection can produce faster genetic gain than intercrop breeding programs which use phenotypic selection, working to a common cost basis that reflects the resources available for a mediumly-invested breeding initiative.…”
Section: Genomic Selection Accuracymentioning
confidence: 99%
“…While these requirements can be easily met within a simulation framework, practical application of a maximum avoidance crossing scheme may be more challenging, as breeders might introduce new genetic material to their breeding population, and not every crossing event might produce seed. Other, more complex, strategies might be more suitable to reduce the loss of genetic variation in real-world breeding programs, such as optimal contribution selection and crossing (Gorjanc et al 2018;Akdemir & Sánchez, 2016;Sonesson et al 2012;Meuwissen, 1997), and exploring these could be a feature of future work.…”
Section: Genomic Selection Accelerates the Reduction Of Intercrop Genmentioning
confidence: 99%